Responses of barley genotypes for salt tolerance under in vitro culture condition (Progressive Agriculture, 2021)
An experiment was undertaken at Agricultural Botany Laboratory, Patuakhali Science and Technology, to screen out salt tolerant barley (Hordeum vulgare L.) genotypes. The evaluation was done based on germination percentage, shoot length, root length and shoot: root ratio. Five barley genotypes including BARI barley 2, BARI barley 3, BARI barley 4, BARI barley 5 and BARI barley 7 were used in the screening program. The barley genotypes were grown in eight levels NaCl solution like 0(Control), 20, 40, 60, 80, 100 and 120 mM. The present study shows that salinity reduced germination percentage of barley and the extent of reduction increased with the increase in the concentration of salinity in the growth medium. Shoot dry weight (1.40 mg), root dry weight (0.21 mg), shoot moisture content (80.0%), root elongation rate (1.81), vigor index (21.30), speed of germination (7.91) and root length (21.67 cm) were obtained from the variety BARI barley 4 with 80 mMNaCL (V3T4). Based on the growth attributes the genotypes BARI barley 7 and BARI barley 4 were found tolerant to salt stress as they grown up to 60 mM and 80 mMNaCl solution respectively. The genotypes BARI barley 4 was therefore selected to be grown in south coastal saline soil of Bangladesh.Progressive Agriculture 32 (1): 1-9, 2021